Optimizing Family Education, Brushing Radicalism Aside - Munardji; Iffatin Nur (Tarbiyah Departement collaboration with AMCA, 2020)
The phenomena of radicalism, including in religiosity, occur in any country and have become a global trend. Their fast widespread is supported by technological development especially in communication and information fields. One of effective ways to deal with radicalism is strengthening the family institution and optimizing its function in shaping the family members’ personality. Sadly, many families become less aware of their importance in exercising such noble function and task. Worse still, some recent radical actions in Indonesia even involved wives and children which reflect the failure of family institution in creating a peaceful and tranquil society where they live in. This paper tries to recall and re-understand the urgency of family institution to educate the family members in facing radicalism. This study is a library research employing the discourse analysis method. The results show that indeed the family institution plays a significant role in shaping their members’ personality and can contribute determinately in brushing radicalism aside and creating a peaceful society.